US REPRESENTATION IN “REMARKS BY PRESIDENT BIDEN ON THE DRAWDOWN OF US ARMY IN AFGHANISTAN” - Arif Umar Hamdani; Trisnowati Tanto (Metahumaniora, 2023)
The US’ decision of leaving Afghanistan, after about 20 years of remaining there in an effort to overthrow the Taliban regime, was phenomenal and caused the world’s negative perspective toward the country. Due to this fact, the study is conducted to open a new critical point of view regarding the issue. The paper mainly discusses the US representation within Joe Biden’s speech entitled “Remarks by President Biden on the Drawdown of US Army in Afghanistan”. van Dijk’s Critical Discourse Analysis (CDA), which deals with power abuse and dominance in the social and political context, is utilized as the main approach in order to reveal the representation of the United States. The discussion will be limited to the micro-level analysis, which comprises macrostructure, microstructure, and superstructure analyses. In the microstructure analysis, two linguistics tools, namely number game and norm expression, will be used. A qualitative descriptive research method is employed and the result of the research shows that the US as the Self is represented positively in the speech. This is shown consistently throughout the macrostructure, microstructure, and superstructure aspects.